Cinema e-Ticket Application Design and Usability Evaluation Using SUS - Marta Lenah Haryanti; Fedelis Fraderic; Sherren Hartono; Jonathan Salim (NUANSA INFORMATIKA, 2025)
The internet has become an essential need in the digital era, facilitating various activities, including e-commerce, supported by advances in Information and Communication Technology (ICT). One form of its implementation is an online cinema ticket booking application, which offers convenience in choosing showtimes, seats, and payments. This study aims to analyze user needs in online cinema ticket booking and design an interface mobile application design that is evaluated using the System Usability Scale (SUS) method. The approach used is User-Centered Design (UCD), which focuses on user experience. The results of the study showed that the evaluation of usability testing with SUS from 30 respondents produced an average score of 81.583 (grade A), which indicates a very good level of application usability. This study recommends the application of the SUS method and the development of a UCD-based design to improve the user experience of the cinema e-ticket application, with the potential for further optimization through variations in evaluation methods and increasing the number of respondents